Specifics of development and approbation of resource saving strategy in agro-industrial complex - Nataliia Gerasymchuk (Tehnologìčnij Audit ta Rezervi Virobnictva, 2017)
The author is grounded the peculiarities of resource saving for the agro-industrial complex, and accordingly - the need to develop the resource-saving strategy specifically for this area of the economy. The author investigates the solution of the scientific problem of the formation of a resource-saving strategy for the agro- industrial complex to ensure the systemic effect of the components of an active resource-saving policy aimed at overcoming the inertia of the influence of the driving forces by the national agricultural producers on the part of the continental and world agriculture and processing markets. In order to understand the readiness of the domestic agro-industrial complex the author makes the investigation of the use of the best practices of the developed resource-saving and resource utilization strategy on the enterprises of the three districts of the Poltava region, and the results are more than satisfactory. Application of the presented strategy will provide a steady growth of the final results of the functioning of the country's agro-industrial complex, implementation of the main directions of the developed strategy will ensure food security of the country, and the use of the integrated mechanisms of resource saving in the agro industrial complex will serve as attractor of the intensification of agro-industrial production which will enable optimization of the processes of resource use and resource efficiency in the form of interactive use of new progressive forms of organization of agricultural producers and processing of agricultural products.